Characterization of Aquifer Poroelastic Response to Impulse and Oscillatory Well Pressure Using Distributed Acoustic Sensing. Issue 1 (4th January 2023) - Becker, Matthew W.; Harris, Brett; Pevzner, Roman
Abstract: The storage of fluids in the subsurface is critical for a broad spectrum of applications including managed aquifer recharge, storage of liquefied carbon dioxide and hydrogen, geothermal heat extraction and exploitation of hydrocarbon. It is surprising then, that there has been relatively little measurement of the vertical distribution of poroelastic storage in geologic formations as compared with permeability. We present experiments in which fluid was injected into an important regional aquifer and the depth‐dependent strain response measured using fiber optic distributed acoustic sensing. The formation expansion and contraction in response to fluid injection were several 100 nanostrain. Strain, and the implied storage distribution, was highly localized in specific strata and demonstrated complex, hydromechanical behavior. This new window into fluid‐geomechanical coupling undermines some typically use models and observations currently in practice, but provides potential for complete representation and prediction of fluid storage in the subsurface. Plain Language Summary: A fiber optic cable was used to measure strain in response to water injection and withdrawal in a sandstone aquifer. The strain was found to be focused in limited strata within the aquifer. In some strata, the formation expanded with injection, and in others the formation contracted with injection. This complex behavior is attributed to the interaction between fluid flow and mechanical strain in the porous rock and is contrary to common models of water storage which predict a proportionate expansion of pore space with injection. These results provide important insight into understanding transient flow response to impulse and oscillatory pressure loading of the well. Key Points: Strain and flow direction was correlated or anti‐correlated with injection head, depending on injection interval Injection and strain behavior was not simply correlated to geophysical or lithologic logs Dynamic injection/withdrawal tests are of limited predictive value to managed aquifer recharge